An overview of the Swedish Education System and supervision - Köksal BOZTAS; Oğuz ER Kemal (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Comparative Education Studies have an important value, especially in educational sciences and the findings from these studies give us useful information regarding the educational practices of various countries. Investigating of the other countries’ educational systems, learning how to solve various problems faced in education in these countries,knowing their curiculum, administration, supervision and educational institutions and their structures can offer us different experiences and perspectives. In this study, Swedish Education System and the Structure of Inspection have been discussed and described through reviewing the related literature